Apakah AI Sebagai Ancaman atau Justru Menjadi Peluang Bagi Dunia Kerja? - Erwin Sya’ban Ardi Wibowo; Andy Andy; Angelin Angelin; I Made Guna Raditya; Leo Alnandez; M. Febri Shahrul Iman (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The rapid advancement of Artificial Intelligence has reshaped the demands of the modern labor market, creating both opportunities and challenges for future job seekers. This study investigates the influence of AI skills on employability, with creativity serving as a mediating variable among senior high school and vocational students in Batam, Indonesia. Using a quantitative research design, data were collected from 186 respondents through an online survey and analyzed with the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The findings reveal that AI skills significantly enhance both creativity and employability. Creativity is also shown to have a positive effect on employability and partially mediates the relationship between artificial intelligence skills and employability. These results indicate that AI literacy, when combined with creative abilities, strengthens students’ adaptability, readiness, and competitiveness in the digital workforce. The study highlights the essential role of creativity as a complementary human skill that amplifies the benefits of artificial intelligence integration in learning. Overall, the research emphasizes the importance of fostering artificial intelligence competencies and creativity development to prepare young individuals for the evolving demands and complexities of future employment.